Production of Mannosylerythritol Lipids Using Oils from Oleaginous Microalgae: Two Sequential Microorganism Culture Approach - Miguel Nascimento; Tiago Coelho; Alberto Reis; Luísa Gouveia; Nuno Faria; Frederico Ferreira (Microorganisms, 2022)
Mannosylerythritol lipids (MELs) are biosurfactants with excellent biochemical properties and a wide range of potential applications. However, most of the studies focusing on MELs high titre production have been relying in the use of vegetable oils with impact on the sustainability and process economy. Herein, we report for the first time MELs production using oils produced from microalgae. The bio-oil was extracted from Neochloris oleoabundans and evaluated for their use as sole carbon source or in a co-substrate strategy, using as an additional carbon source D-glucose, on Moesziomyces spp. cultures to support cell growth and induce the production of MELs. Both Moesziomyces antarcticus and M. aphidis were able to grow and produce MELs using algae-derived bio-oils as a carbon source. Using a medium containing as carbon sources 40 g/L of D-glucose and 20 g/L of bio-oils, Moesziomyces antarcticus and M. aphidis produced 12.47 ± 0.28 and 5.72 ± 2.32 g/L of MELs, respectively. Interestingly, there are no significant differences in productivity when using oils from microalgae or vegetable oils as carbon sources. The MELs productivities achieved were 1.78 ± 0.04 and 1.99 ± 0.12 g/L/day, respectively, for M. antarcticus fed with algae-derived or vegetable oils. These results open new perspectives for the production of MELs in systems combining different microorganisms.